Heoretical approach to singl e - mode operation of bistable fabry - perot laser containing saturable absorber - Bao, Phung Quoc; Hoang, Dinh Van (VNU Journal of Science: Mathematics - Physics; Vol 18 No 1, 2002)
Abstract